SELF-REGULATED LEARNING DAN PENYESUAIAN DIRI DENGAN SOMATISASI PADA MAHASISWA TINGKAT AKHIR - Widya Puteri, Ika Apriati; Latifah, Nurul; Indah Muslimah, Alfiana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
This study aims to determine the relationship between selfregulated learning and adjustment to somatization in final year students at the Islamic University